MODERNISASI PENDIDIKAN PESANTREN DI INDONESIA (Studi Pemikiran K.H. Imam Zarkasyi) - Millah, Saepul; Daryaman, Daryaman (Jurnal Penelitian Pendidikan Islam, 2017)
The challenge of the pesantren world is getting bigger in the present and the future. Along with globalization, pesantren is faced with some inevitable cultural and social changes. And as a consequence, pesantren must provide mutualistic response. Technological advances have penetrated the fortress of pesantren culture. One of them is modernization by most pesantren now. One of them is applied by temporary Gontor hut ie K.H. Imam Zarkasyi. Modernization itself is a change for the sake of improvement in accordance with the ability of the surrounding community, a condition in accordance with the state of the age without losing the meaning of uniqueness and authenticity. The research method used is literature research or library research, research is done by using literature (literature), either in the form of books, notes or reports of previous research results. The results of this study indicate that K.H. Zarkasyi priest strongly affects several pesantrens in Indonesia.